Absence of microsatellite instability in extramammary Paget's disease. Issue 3 (5th May 2021) - Kashiwada‐Nakamura, K.; Myangat, T. M.; Kajihara, I.; Kusaba, Y.; Tanaka, K.; Sakamoto, R.; Maeda‐Otsuka, S.; Yamada‐Kanazawa, S.; Sawamura, S.; Kanemaru, H.; Nishimura, Y.; Honda, N.; et al.
Abstract: Background: Deficiency of DNA mismatch repair (MMR) induces microsatellite instability (MSI). Pembrolizumab, an antibody targeting PD‐1 (an immune checkpoint inhibitor), is more effective against MMR‐deficient tumours than against MMR‐proficient tumours. The status of MMR is a useful biomarker for predicting the effectiveness of pembrolizumab administration. Although the status of MMR has attracted attention in skin tumours, there are few reports on MSI in extramammary Paget's disease (EMPD). Objectives: To evaluate the status of MMR in patients with EMPD. Materials & Methods: One hundred one patients with EMPD were included. MMR status of the genomic DNA of each subject was analysed using Promega panel (approved as a companion diagnostic agent for the administration of pembrolizumab). Results: MSI testing showed the occurrence rates of MSI‐high (more than two markers are unstable), MSI‐low (one marker is unstable) and MSS (all markers are stable) tumour tissues were 0% (0/101), 1.0% (1/101) and 99.0% (100/101), respectively. Conclusion: The status of MMR may not be useful for the potential therapeutic application of pembrolizumab. Abstract : To evaluate the status of DNA mismatch repair in patients with extramammary Paget's disease (EMPD), 101 skin samples were analyzed using Promega panel (approved as a companion diagnostic agent for the administration of pembrolizumab). MSI testing showed the occurrence rates of MSI‐high (more than two markers are unstable), MSI‐low (one marker is unstable), and MSS (all markers are stable) tumor tissues were 0% (0/101), 1.0% (1/101), and 99.0% (100/101), respectively. The status of MMR may not be useful for the potential therapeutic application of pembrolizumab.